2010
DOI: 10.1007/s00383-010-2696-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the Rehbein procedure obsolete in the treatment of Hirschsprung’s disease?

Abstract: PurposeAfter 25 years of practice and positive results of the Rehbein-procedure (RB) for children with Hirschsprung Disease (HD), we changed to the less invasive transanal endorectal pull through (TERPT). The aim of this study was to compare short- and mid-term complications of these two procedures in our patients with HD.MethodsRetrospective data of 50 HD patients were analyzed. Of these patients, 25 underwent RB (2000–2006) and in 25 the TERPT was performed (2005–2009). Medical records were reviewed to score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…All other dehiscences healed uneventfully after resuturing. Visser et al reported a nearly similar incidence of anastomotic leakage for the transabdominal pull-through procedure (16%) and a lower leakage rate for TERPT (4%) [16]. In our study, the dehiscence was detected by a standardized routine examination.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…All other dehiscences healed uneventfully after resuturing. Visser et al reported a nearly similar incidence of anastomotic leakage for the transabdominal pull-through procedure (16%) and a lower leakage rate for TERPT (4%) [16]. In our study, the dehiscence was detected by a standardized routine examination.…”
Section: Discussionsupporting
confidence: 64%
“…This reflects a considerable but not significantly better outcome in favor of the TERPT group (p=0.09). Comparable reports achieved similar results [2,6,16,17]. The incidence in the literature ranges from 6% to 27% for TERPT and 6-59% for transabdominal pull-through procedures regarding persistent postoperative constipation [2,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The other technique is the complete transanal endorectal pull-through introduced by de La Torre and Langer [5,6]. Both techniques have proven to be preferable to the open techniques [7][8][9][10]. It has not been clarified whether the best results are accomplished by the laparoscopically assisted transanal pull-through or the complete transanal pull-through.…”
mentioning
confidence: 99%
“…A Rehbein procedure may not be the currently preferred technique for HD. In their study Visser et al even suggested that the Rehbein procedure is obsolete, preferring to perform a transanal endorectal pull-through with a short muscle cuff [ 16 ] . Follow-up of our patients with residual aganglionosis after an initial Rehbein procedure revealed that half of them (n = 2) were completely continent; however, one suff ered from mild obstructive symptoms.…”
Section: Results ▼mentioning
confidence: 99%